Determinants of survival in children with cancer in Johannesburg, South Africa - Nadia Beringer (AOSIS, 2021)
Background: Childhood cancer, although rare, remains an important cause of death worldwide. The outcomes of children with all cancer types in South Africa are not well-documented.